IL-33 triggers lung autophagy in anaphylaxis mice models - Nawal Zakaria Haggag; Nashwa Ahmed El-Shinnawy; Gamal Badr; Hany N. Yousef; Sahar Sobhy Abd-Elhalem (Journal of Basic and Applied Zoology)
Abstract Background The relationship between the alarming cytokine interleukin-33 (IL-33) and lung autophagy in systemic anaphylaxis mouse models is not yet fully elucidated, hence, the current study attempts to explain the regulation of lung autophagy in systemic anaphylactic mouse models. IL-33 plays a critical role in endoplasmic reticulum (ER) stress and autophagy regulation via insulin-like growth factor-binding protein-3 (IGFBP-3). Results The results of the present study confirmed the induction of systemic anaphylaxis in mice through the elevated mast cell mediators in the peritoneal lavage. Consequently, lung stress triggered IL-33 secretion that influenced autophagy markers; IGFBP-3, activating transcription factor-6 (ATF-6), autophagy related gene 4B (ATG4B), p62, microtubule-associated protein light chain3-II (LC3-II) as well as DNA damage-regulated autophagy modulator 1 (DRAM1). Conclusion This research is a trial to investigate lung autophagy in compound 48/80 or ovalbumin-induced systemic anaphylaxis mouse models and pay a particular attention to the role of IL-33 in lung autophagy in such models. Graphical abstract